HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN TINGKAT KECEMASAN KELUARGA (CAREGIVER) PASIEN YANG MENJALANI KEMOTERAPI - Sukma " Nirmala; Safri " "; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Professional nursing practice holds a very important role in providing nursing care to patient and family. Effective communication can reduce the anxiety experienced by the family of chemotherapy patients. The aim of this research was to identify the correlation between therapeutic communication the nurse with the anxiety level of family (caregiver) on chemotherapy patient. The design was descriptive correlational research with cross sectional approach. The sampling technique purposive sampling involving 84 family (caregiver) of chemotherapy patients in Anyelir room of Arifin Achmad Hospital Riau Province, that was selected based on inclusion criteria. This research used questionnaire that already tested for validity and reliability. This research using univariate and bivariate analysis with chi-square test. The results showed that p value was 0,008 (p value < 0,05), which means that there is a correlation between therapeutic communication the nurse with the anxiety level of family (caregiver) on chemotherapy patients. The results expected to nurse in order to maintain and improve therapeutic communication to minimize the anxiety of family (caregiver) on chemotherapy patients. Keyword: Anxiety, the family of chemotherapy patient, therapeutic communication